Integrative assessment of kick boxers’ brain blood circulation and bio-electrical activity in conditions of correction technologies’ application - Y.N. Romanov; A.P. Isaev; A.V. Shevtsov; L.A. Romanova; M. Cieslicka; R. Muszkieta (Physical Education of Students)
Purpose: to scientifically substantiate the role of para-vertebral impacts on blood circulation and bio-electrical activity of kick boxers’ cortex. Material: in the research participated kick boxers (main group, n=62) and university students (control group, n=25) of 18-23 years’ age. Assessment of para-vertebral impacts with device Armos and classic massage was fulfilled with the help of the following methodic: trans-cranial dopplerography of head main arteries and cortex EEG of the tested. Results: it was found that with the help of para-vertebral impacts by device Armos linear velocity of cerebral blood flow reduces to normal limits and in- and inter-hemispheres’ interaction strength increases. Conclusions: para-vertebral impacts by device Armos activate integrative processes and inter-hemispheres’ interactions of different cortex areas of kick boxers. It can witness about better formation of functional systems, ensuring sports efficiency.